Liver volumetry improves evaluation of treatment response to hepatic artery infusion chemotherapy in uveal melanoma patients with liver metastases - Zensen Sebastian; Steinberg-Vorhoff Hannah L; Milosevic Aleksandar; Richly Heike; Siveke Jens T; Opitz Marcel; Haubold Johannes; Li Yan; Forsting Michael; Schaarschmidt Benedikt Michael (Radiology and Oncology)
In uveal melanoma patients, short-term evaluation of treatment response to hepatic artery infusion chemotherapy (HAIC) using the Response Evaluation Criteria in Solid Tumors (RECIST) 1.1 criteria is challenging due to the diffuse metastatic spread. As liver enlargement can frequently be observed, this study aims to compare RECIST 1.1 and liver volumetry (LV) for the evaluation of HAIC treatment response.